An Overview of Multi-Energy Microgrid in All-Electric Ships - Huang, Yuqing; Wang, Liangxiu; Zhang, Yuanwei; Wang, Le; Zhao, Zhangfei (Frontiers in Energy Research, 2022)
Owing to the severe fossil energy shortage and carbon pollution, the extensive electrification of maritime transportation, represented by all-electric ships (AESs), has become an appealing solution to increase the efficiency and environmental friendliness of the industry. To improve energy utilization, not only renewable energy but also thermal energy has been introduced is used in AESs. However, various uncertainties that are associated with renewable energy and ship motions significantly inhibit and complicate the operation and navigation of multi-energy shipboard microgrids. Accordingly, a new coordination of optimal energy management and voyage scheduling is important in reducing both the costs and emissions of AESs. This overview characterizes shipboard microgrids and several emerging technical challenges related to joint power and voyage scheduling, and elucidates prospects for further research, based on a comprehensive survey of the relevant literature.